My recommendation would be to factor..
x² + 4x + 3 = 0 factor the left side into two binomials
(x + 3)(x + 1) = 0 set each of these binomials equal to zero and solve
x + 3 = 0 Implies x = -3
x + 1 = 0 implies x = -1
Answer:
4
Step-by-step explanation:
I took the quiz, here's proof
Answer:
Read the excerpt from "Digging"The cold smell of potato mould, the squelch and slapOf soggy peat, the curt cuts of an edgeThrough living roots awaken in my head.But I’ve no spade to follow men like them.Between my finger and my thumbThe squat pen rests.I’ll dig with it.Read the haiku by Bashō. When the winter chrysanthemums go,there’s nothing to write about but radishes.What common concern do these poems share?
Step-by-step explanation:
Read the excerpt from "Digging"The cold smell of potato mould, the squelch and slapOf soggy peat, the curt cuts of an edgeThrough living roots awaken in my head.But I’ve no spade to follow men like them.Between my finger and my thumbThe squat pen rests.I’ll dig with it.Read the haiku by Bashō. When the winter chrysanthemums go,there’s nothing to write about but radishes.What common concern do these poems share?
System of Linear Equations entered :
[1] 5x - 6y = 7
[2] 6x - 7y = 8
Graphic Representation of the Equations :
-6y + 5x = 7 -7y + 6x = 8
Solve equation [2] for the variable x
[2] 6x = 7y + 8
[2] x = 7y/6 + 4/3
// Plug this in for variable x in equation [1]
[1] 5•(7y/6+4/3) - 6y = 7
[1] - y/6 = 1/3
[1] - y = 2
// Solve equation [1] for the variable y
[1] y = - 2
// By now we know this much :
x = 7y/6+4/3
y = -2
// Use the y value to solve for x
x = (7/6)(-2)+4/3 = -1
0.3 x 103 = 30.9
0.3 x 1025 = 307.5
3 x 10^5 = 300,000